Answer:
x = 3, y = 3, z = - 2
Explanation:
Given the 3 equations
x - y - 2z = 4 → (1)
- x + 3y - z = 8 → (2)
- 2x - y - 4z = - 1 → (3)
Add (1) and (2) term by term to eliminate x
2y - 3z = 12 → (4)
Multiply (1) by 2 and add to (3) to eliminate x
2x - 2y - 4z = 8 → (5)
Add (3) and (5) term by term to eliminate x
- 3y - 8z = 7 → (6)
Multiply (4) by 3 and (6) by 2
6y - 9z = 36 → (7)
- 6y - 16z = 14 → (8)
Add (7) and (8) term by term to eliminate y
- 25z = 50 ( divide both sides by - 25 )
z = - 2
Substitute z = - 2 into (7)
6y + 18 = 36 ( subtract 18 from both sides )
6y = 18 ( divide both sides by 6 )
y = 3
Substitute y = 3 and z = - 2 into (1)
x - 3 + 4 = 4
x + 1 = 4 ( subtract 1 from both sides )
x = 3
Solution is x = 3, y = 3, z = - 2